A autoeficácia no uso e desenvolvimento de tecnologias: uma iniciativa com meninas do ensino médio - Mattos, Francielle de (2018)
Labor market in the area of Information Technology (IT) is still dominated by male professionals. Despite being a field with a lot of job offer, studies indicate that girls, throughout the school years, are discouraged to pursue a career in such field, which is perceived as a “boy thing”. Thus, there is a global effort to present the Computing field to girls during the school period, in order to mitigate the problem of labor sexual division and the misogyny present in this field. For that, one of the main approaches adopted is the training through the teaching of basic concepts of Computation, logical reasoning, the principles of computer programming, computational thinking, as well as lectures and contact with female professionals in the IT field. Thus, this project aims to verify if such approaches applied in an exclusive female course can increase the levels of self-efficacy in relation to the technology domain. In this course, collaborative projects were implemented, aimed at developing leadership and self-confidence in students, practicing the acquired knowledge and demonstrating the potential of applying technologies to solve real-world problems. To collect data, we applied questionnaires and interviews, in addition to class reports and analysis of the activities carried out during the course. With the questionnaires, data related to the profile of the students and their professional interests, technical knowledge about computational thinking, the profile in relation to the use of technological tools and the self-efficacy in the domain and development of computational solutions, besides the opinion about the course and the contact with professionals. During the study, the activities carried out were recorded, with information about the contents teached, observations, comments and reports of the students during the activities. The interviews were carried out semi-structured at different times of the research period. Interview reports will be recorded in the class journals and participants’ registrations will also be considered in the Facebook and Whatsapp social network groups created to exchange experiences among participants. The collected privacy sensitive data were stored in a password protected manner, in which only the researchers involved had access. The initiative also promoted the students’ contact with professional women in the area of computing, in a supportive and feminine environment, allowing the students to develop self-efficacy and competence in the area of Computing through the teaching of programming. Finally, it was verified from the critical analysis of the data collected that this intervention showed signs that the approaches used can generate an approximation of the participants to the Computing area, minimizing the stereotypes and cultural and social myths associated with misogyny in this career.